The Influence of Regional Socioeconomic Features On the Distribution of Financial Resources For Higher Education - Yang Yu; Wang Xinxin; Li Ruoxi; Yin Tingting (SocioEconomic Challenges, 2024)
The article is devoted to solving the problem of “budgetary financial adequacy of higher education” in China through a fairer, uniform, and sufficient distribution of financial costs for higher education among the provinces of this country, considering significant differences in the natural, economic, and social conditions of development in various regions. Currently, in China, the calculation of standard financial costs for the education sector is carried out according to the legal requirements of the Budget Department of the Ministry of Finance, taking into account the number of people studying at the corresponding level of education, the cost norm for this level of education, and the deviation coefficient. Instead, this article proposes a more comprehensive and rational approach that considers regional differences in the cost of living and the financial burden on higher education institutions, increasing the government’s responsibility for supporting a balanced distribution of financial resources for higher education. To take into account regional differences, it is proposed to use a system of indices for the difference in the costs of regional development, which includes three main categories of indicators: natural factors (the complexity of the terrain and the share of the area planted with forests), economic factors (the index of prices for raw materials, GDP per capita, freight traffic, and the total duration of operation of urban public transport), and social factors (population density in municipal areas, number of graduates of general education colleges and universities). To determine the fair size of budgetary expenditures on higher education, it is proposed to make adjustments to the index of differentiation of regional development expenditures, which combines these indicators using the geometric regression average benchmark method (without including a constant term). A higher value of this index means that the region needs more resources to achieve the same level of development as another region, so the standard budget expenditures for higher education should be higher for it. For all provinces in China, the coefficient of financial adequacy of higher education was calculated as the ratio between the standard financial costs of higher education (calculated according to the proposals outlined in this article) and the actual costs incurred. It is proposed that this coefficient be used as a basis for optimizing their distribution. The article emphasises the need to form a strategy for financing higher education in China, which should be based on a dynamic permanent adjustment of the amount of allocated financial resources depending on changes in the regional social and economic conditions of development of each province, an effective institutional mechanism that would allow adapting this strategy to endogenous and endogenous changes in China’s economy, optimisation of horizontal transfer payments and partnership assistance programs, and incentive mechanisms for local governments to invest in higher education.